Examining the role of religiosity in shaping ethical perceptions of creative accounting among accounting students - Putri, Caesar Marga; Rahmawati, Novita; Bashir, Usman (Journal of Accounting and Investment, 2025)
Research aims: This study examines the role of religiosity in shaping accounting students' ethical views on creative accounting and compares perceptions between students from religious and non-religious universities.Design/Methodology/Approach: The quantitative method is used in this research. Primary data was obtained from the questionnaire. This research was conducted in two universities in Yogyakarta, Indonesia. A total 157 data were analyzed using regression analysis and independent sample t-test.Research findings: The results show that religiosity does not significantly affect accounting students' ethical views on creative accounting, nor is there a notable difference between students from religious and non-religious universities.Theoretical contribution/ Originality: This study contributes to the existing body of knowledge in accounting ethics by challenging the commonly held assumption that religiosity significantly influences ethical perceptions. By demonstrating that students from both religious-based and non-religious-based universities hold similar views on creative accounting it provides new insights into the complex relationship between ethical judgment and institutional or religious backgrounds.Practitioner/Policy implication: The findings suggest that ethics education in accounting should not only depend on religious or institutional identity but instead focus on case-based learning, critical thinking, and real-world dilemmas across all universities. Based on a comparative study of students from religious and non-religious settings, it shows that religiosity alone may not determine ethical perceptions, highlighting the influence of other factors.Research limitation/Implication: Religiosity was not deeply explored in its multidimensional aspects. In this research, religiosity was measured using religious affiliation, which might not fully capture the extent of individual religiosity.